The Legal Analysis Of Electronic Medical Consent In The Inpatient Department Of RS PKU Muhammadiyah Petanahan - Yunengsih, Yuyun; Aulia Rahma, Syifa (Sean Institute, 2024)
As technology advances, all fields are compelled to transition from manual to electronic processes, including informed consent. The implementation of electronic informed consent requires an examination of its execution and usage. Electronic signatures are used for verification and authentication in clinical information recording and documentation. From a legal perspective, medical records need validity to be used as legal evidence. RS PKU Muhammadiyah Petanahan has implemented informed consent using electronic signatures in the form of barcodes. This study aims to determine the validity of using electronic signatures on informed consent, as well as its security and privacy aspects. This research employs a qualitative method with an ethnographic design. The results show that the type of electronic signature used is a non-certified electronic signature in the form of a barcode. This signature was chosen because it facilitates healthcare workers in completing informed consent documents and its creation process is relatively easy and affordable. Currently, the regulation referenced for the use of electronic signatures in electronic medical records at RS PKU Muhammadiyah Petanahan is Law No. 19 of 2016 on Information and Electronic Transactions. In terms of security, electronic informed consent data is stored in a database on a computer server. Regarding privacy, there is a Standard Operating Procedure (SPO) that governs its use. Non-certified electronic signatures on medical records potentially pose a security risk. Therefore, based on the research results, it is recommended to change the type of electronic signature to a certified electronic signature